The student-computer interface on an intelligent tutoring system for Japanese language instruction - Maciejewski, Anthony A., author; IEEE, publisher (Colorado State University. Libraries, 1989)
This work describes the human-computer interaction of an intelligent tutoring system designed to mediate some of the difficulties of acquiring proficiency in reading technical Japanese material.
Keywords: user interfaces; knowledge based systems; computer aided instruction